ELISPOT and functional T cell analyses using HLA mono-specific target cells. - Horlock, C; Stott, B; Dyson, J; Ogg, G; Mcpherson, T; Jones, L; Sewell, A; Wooldridge, L; Cole, D; Stebbing, J; Savage, P (2009)
Simple T cell assays specific for any chosen HLA class I or class II/peptide combination, are of enormous value in cancer immunotherapy, clinical trials, vaccine and infectious disease research. The reliable measurement of T cell activity can be difficult due to the presence of other alleles on target cells, particularly for the non-HLA-A2 alleles, and the varying baseline characteristics of the different APCs employed. In the absence of pulsing with HLA-A2 restricted peptides, T2 cells are functionally HLA class I and II negative. By coating these cells with recombinant HLA peptide complexes, HLA mono-specific cells are produced that present only a defined single epitope, and generate minimal background immune activation. In ELISPOT, intracellular cytokine staining (ICS) and killing assays using T cells specific for HLA-A2/peptide complexes, the HLA mono-specific cells gave comparable results, to those using standard peptide pulsed HLA-A2 positive T2 cells without significant background. Successful T cell assays for non-HLA-A2 T cells were also performed, with PBMCs recognizing HLA-A24 and HLA-DR15/peptide complexes. The data, obtained with ELISPOT, ICS and FACS-based killing assays, all demonstrate high specificity of T cell activity and low levels of background activity. HLA mono-specific cells are simple to prepare, and can be used with any stable recombinant HLA allele/peptide combination; providing a useful system for improved T cell functional analyses across all HLA allotypes. This represents a significant advance in the generation of reliable functional T cell data.